A plain linear rule for fatigue analysis under natural loading considering the sequence effect. (October 2017) - Calderon-Uriszar-Aldaca, I.; Biezma, M.V.
Highlights: A review of sequence effect in fatigue by linear and non-linear rule approaches. Assessment of non-linear approach suitability for natural random loadings analysis. Determination of accelerating factor for equivalent damage by linear-rule approach. Linear-rule suitability for natural random loads considering structural reliability. Simplicity and suitability demo case with a representative structural element. Abstract: Fatigue under variable amplitude loading is currently assessed with the Palmgren-Miner rule in structural standards, ignoring the order of loading, which would require non-linear or mixed rules, especially for the random loading sequences applied to certain structures. Therefore, the goal is to develop a practical and simple correction factor ensuring the linear summation of damage is conservative, so as to take the sequence effect into account in random loading from natural sources. The theoretical consistency of this approach is demonstrated and a case study is developed to test the feasibility of the new rule and its simplicity.